Effects of chin-up posture on the sequence of swallowing events - Calvo, Irene (Head Neck, 2017)
BACKGROUND: Chin-up posture is frequently used to manage oral dysphagia after head and neck cancer. This prospective study investigates the effects of chin-ups on the sequence of pharyngeal swallowing events. METHODS: Twelve healthy young adults performed 45 consecutive swallows of 5 mL water across 3 phases on videofluoroscopy: 5 swallows in the neutral head position; 30 swallows during chin-up posture; and 10 swallows in the neutral head position. Swallowing kinematic and bolus flow measures for 9 swallowing events were recorded. Linear trends were analyzed across 30 chin-up swallows; pairwise comparison was used to compare the 3 phases. RESULTS: Time to hyoid peak and laryngeal vestibule closure changed abruptly during chin-up swallowing compared to the initial neutral position. No measure changed across 30 chin-up swallows. Time of hyoid burst decreased upon returning to the neutral position. CONCLUSION: Our findings indicate that chin-up posture challenges the pharyngeal sequence of events for both swallowing kinematics and bolus flow.